Optimization of high pressure processing parameters to preserve quality attributes of a mixed fruit and vegetable smoothie - Fernandez, María Verónica; Denoya, Gabriela Inés; Agüero, Maria Victoria; Jagus, Rosa Juana; Vaudagna, Sergio Ramon (2018)
Fruit & Vegetable (F&V) smoothies are rich in nutrients and other health related compounds. However, they have a short shelf-life and the traditional methods applied to preserve them generate losses in their natural flavor and nutrients. The aim of this study was to optimize the pressure level (35–650 MPa) and holding time (1–9 min) of High Pressure Processing (HPP), performed at an initial temperature of 20 °C and only modified by adiabatic heating of a F&V smoothie in order to achieve microbial and enzymatic inactivation while maintaining its natural attributes. Response surface methodology with a Doehlert design and Desirability function were employed to simultaneously optimize these quality attributes. Results showed that HPP enhances microbial quality and does not affect pH, total soluble solids, texture and total phenolic content. Moreover, the optimal HPP treatment (627.5 MPa/6.4 min) leads to reductions of 85%, 45% and 10% on PME, POD and PPO, increases antioxidant capacity by 75% and maintains or slightly improves the color of the smoothie.